6-Substituted quinolines as RORγt inverse agonists. Issue 23 (1st December 2017) - Barbay, J. Kent; Cummings, Maxwell D.; Abad, Marta; Castro, Glenda; Kreutter, Kevin D.; Kummer, David A.; Maharoof, Umar; Milligan, Cynthia; Nishimura, Rachel; Pierce, Joan; Schalk-Hihi, Celine; Spurlino, John; et al.
Graphical abstract: Abstract: We identified 6-substituted quinolines as modulators of the retinoic acid receptor-related orphan receptor gamma t (RORγt). The synthesis of this class of RORγt modulators is reported, and optimization of the substituents at the quinoline 6-position that produced compounds with high affinity for the receptor is detailed. This effort identified molecules that act as potent, full inverse agonists in a RORγt-driven cell-based reporter assay. The X-ray crystal structures of two full inverse agonists from this chemical series bound to the RORγt ligand binding domain are disclosed, and we highlight the interaction of a hydrogen-bond acceptor on the 6-position substituent of the inverse agonist with Glu379:NH as a conserved binding contact.